Pengabdian Budidaya Garam Dan Dampak Dari Peluasan Wilayah Tambak Garam Beserta Penanaman Pohon Di Desa Galis Kec. Gili Genting - Ali Armadi; Muhammad Misbahudholam AR; Abdullah hasan AS; Ahmad Shahibul Wafa; Moh. Yasir; Moh. Khairul Fattah; Fadila Fadila (Universitas Muhammadiyah Manado, 2023)
Salt is an important staple both in the body and as an ecosystem. The same as reforestation is done in order to protect the environment and can prevent the negative impact of salt cultivation which results in changes in weather that is very hot than usual, community service carried out by KKN (Real Work Lectures). ) from STKIP PGRI Sumenep for the 2023/2024 academic year which is placed in the village of Galis Giligenting with the theme